Lentiviral labeling of mouse and human enteric nervous system stem cells for regenerative medicine studies. Issue 10 (8th September 2014) - Natarajan, D.; Cooper, J.; Choudhury, S.; Delalande, J.‐M.; McCann, C.; Howe, S. J.; Thapar, N.; Burns, A. J.
Abstract Background Reliable methods of labeling human enteric nervous system (ENS) stem cells for use in novel cell replacement therapies for enteric neuropathies are lacking. Here, we explore the possibility of using lentiviral vectors expressing fluorescent reporter genes to transduce, label, and trace mouse and human ENS stem cells following transplantation into mouse gut. Methods Enteric nervous system precursors, including ENS stem cells, were isolated from enzymatically dissociated mouse and human gut tissues. Lentivirus containing eGFP or mCherry fluorescent reporter genes was added to gut cell cultures at a multiplicity of infection of 2–5. After fluorescence activated cell sorting for eGFP and subsequent analysis with markers of proliferation and cell phenotype, transduced mouse and human cells were transplanted into the gut of C57BL/6 and immune deficient Rag2‐/gamma chain‐/C5 mice, respectively and analyzed up to 60 days later. Key Results Mouse and human transduced cells survived in vitro, maintained intense eGFP expression, proliferated as shown by BrdU incorporation, and formed characteristic neurospheres. When transplanted into mouse gut in vivo and analyzed up to 2 months later, transduced mouse and human cells survived, strongly expressed eGFP and integrated into endogenous ENS networks. Conclusions & Inferences Lentiviral vectors expressing fluorescent reporter genes enable efficient, stable, long‐term labeling of ENS stem cells when transplanted into in vivo mouse gut. This lentiviral approach not only addresses the need for a reliable fluorescent marker of human ENS stem cells for preclinical studies, but also raises the possibility of using lentiviruses for other applications, such as gene therapy.